Application of LQR theory to modular current-programmed buck converters. (1st January 2015) - Al-Mothafar, Mohammed R.D.; Radaideh, Saleh M.; Radaydeh, Nuha M.
This paper investigates the application of the linear-quadratic regulator (LQR) theory to modular current-mode-controlled (CMC) pulse-width-modulated (PWM) dc-dc converters operating in the continuous conduction mode. Small-signal models are used in conjunction with the LQR technique to design new feedback controllers for a two-module parallel-input series-output step-down (buck) dc-dc converter under two different control schemes. The dynamic responses are compared with those obtained using the classical control approach. Cycle-by-cycle simulations are performed to validate the analysis.